PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP TINGKAT PEMAHAMAN AKUNTANSI (Studi Empiris Pada Mahasiswa Jurusan Akuntansi Fakultas Ekonomi Universitas Tanjungpura Pontianak Angkatan 2008-2010) - Ichwan B41109144, Sodik Nur (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2014)
This study is a replication of previous studies by HersanAnanto (2008) andAnggunYuniani ( 2010). The purpose of this study is to find out the effect of emotional intelligence, spiritual intelligence towards understanding of accounting. This study uses primary data that obtained from the survey directly to the object of research through questionnaires. The population used in this study are students of the Faculty of Economics, University Tanjungpura who has completed a minimum of 120 credits. The samples used were 32 students who have been finished at least 120 credits. Emotional intelligence is measured by using aspects of self-identification, self-control, motivation, empathy and social skills. Spiritual intelligence is measured by using aspects of The GodÂ  principle, the trust principle, leadership principle, the principle of learner -minded, future-oriented principle and the principle of regularity. Understanding of accounting measured by the value of principle accounting 1, principle accounting 2, intermediate accounting 1, intermediate accounting 2, advanced accounting 1, advanced accounting 1, auditing 1, auditing 2 and accounting theory.The resultsof thehypothesis observation show that emotional intelligence has a significant effect onÂ  understanding of accounting, while the spiritual intelligence does not have a significant impact on the Understanding of Accounting. Keywords ; emotional intelligence, spiritual intelligence, understanding of accounting